Α, β‐Double Electrophilic Addition of Allene‐1, 3‐Dicarboxylic Esters for the Construction of Polysubstituted Furans by KI/tert‐Butyl Hydroperoxide (TBHP)‐Promoted Oxidative Annulation. Issue 27 (25th May 2016) - Li, Hong‐Liang; Wang, Yu; Sun, Pei‐Pei; Luo, Xiaoyan; Shen, Zhenlu; Deng, Wei‐Ping
Abstract: An unprecedented KI/ tert ‐butyl hydroperoxide promoted tandem Michael addition/oxidative annulation of allene‐1, 3‐dicarboxylic esters and 1, 3‐dicarbonyl compounds has been developed. This procedure provides a new, facile, and transition‐metal‐free synthetic approach to afford polysubstituted furans in moderate to excellent yields (up to 93 %). This method first establishes a α, β‐double electrophilic reaction mode of allene‐1, 3‐dicarboxylic esters to form 1, 3‐dicarbonyl compounds. Abstract : Ring formation : An unprecedented KI/ tert ‐butyl hydroperoxide (TBHP)‐promoted tandem Michael addition/oxidative annulation of allene‐1, 3‐dicarboxylic esters and 1, 3‐dicarbonyl compounds has been developed (see scheme). This provides a new, facile, and transition‐metal‐free synthetic approach to polysubstituted furans in moderate to excellent yields.